Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.clnesp.2021.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and feeding practices and tolerance during the acute and late phase of critically ill COVID-19 patients

Abstract: Background & aims: Different metabolic phases can be distinguished in critical illness, which influences nutritional treatment. Achieving optimal nutritional treatment during these phases in critically ill patients is challenging. COVID-19 patients seem particularly difficult to feed due to gastrointestinal problems. Our aim was to describe measured resting energy expenditure (mREE) and feeding practices and tolerance during the acute and late phases of critical illness in COVID-19 patients. Methods: Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 53 publications
3
71
1
2
Order By: Relevance
“…Therefore, upon ICU admission, nutritional assessment is mandatory. An individualized approach including indirect calorimetry is recommended, because persistent hypermetabolism was observed in these patients [ 130 , 131 ].…”
Section: Tailoring Mnt To the Individual Patient’s Needsmentioning
confidence: 99%
“…Therefore, upon ICU admission, nutritional assessment is mandatory. An individualized approach including indirect calorimetry is recommended, because persistent hypermetabolism was observed in these patients [ 130 , 131 ].…”
Section: Tailoring Mnt To the Individual Patient’s Needsmentioning
confidence: 99%
“…3 They also observed that the hypermetabolism persisted beyond 1 week post-ICU admission. 3 Others have suggested that the hypermetabolism may be sustained for 3 weeks post-ICU admission. 4 Disease conditions exhibiting hypermetabolism are generally associated with increased net protein catabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Adjusted body weight was calculated in the ESPEN guidelines by: ideal body weight + ([actual weight -ideal body weight] × 0.25) 26 Recent indirect calorimetry studies demonstrate many critically ill patients with COVID-19 exhibit hypermetabolism. [3][4][5] One study indicated that hypermetabolism (measured energy expenditure > 110% of predicted) occurred in two-thirds of their patients. 3 They also observed that the hypermetabolism persisted beyond 1 week post-ICU admission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations